2020
DOI: 10.1155/2020/5342606
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Complexity Game of Supply Chain Green Innovation Introduction under EPR Policy and Government Subsidies

Abstract: Nowadays, with global scientific and technological levels rapidly improving, innovation has been a great need for enterprises to solve the dilemma. Combined with EPR (Extended Producer Responsibility) and the topic of remanufacturer, adopting green innovation has been an effective way when green supply chain management is applied. In this paper, we focus on the activity of green innovation and build a model where the manufacturer will invest in green innovation to improve the product availability rate of recyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…We can get from Figure 16 that the delayed feedback method can not effectively control the two nonlinear systems in this paper. is is contrary to the research results of chaos control in [49], which means that we consider that the efficiency of the delayed feedback control method is higher than that of the parameter adjustment control method.…”
Section: Chaos Controlcontrasting
confidence: 77%
See 2 more Smart Citations
“…We can get from Figure 16 that the delayed feedback method can not effectively control the two nonlinear systems in this paper. is is contrary to the research results of chaos control in [49], which means that we consider that the efficiency of the delayed feedback control method is higher than that of the parameter adjustment control method.…”
Section: Chaos Controlcontrasting
confidence: 77%
“…It is necessary to take some measures to delay or eliminate chaos and benefit the whole system. ere are many methods to control chaos, namely, delayed feedback control [34,46], variable feedback control [47,48], and parameter adjustment [49]. In this section, the parameter adjustment method and delay control method are adopted to control the market prices of participants.…”
Section: Chaos Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…e Organization for Economic Co-operation and Development (OECD) views technological innovation as comprising new products or services and the making of significant changes in the products and processes, and innovation is realized when the new product or service is introduced in the market [1]. Technology innovation is the driving force in promoting economic growth [2][3][4][5], particularly so for developing economies. In the case of China, the 18 th Party Congress of China put forward the implementation of innovation driven development strategy and stressed that technology innovation is the strategic support for improving social productivity and overall national strength and must be put at the heart of the overall national development.…”
Section: Introductionmentioning
confidence: 99%
“…Government subsidy plays a role in developing the economy, promoting enterprise technology or product innovation and reducing poverty. Research on government subsidy mainly focuses on low-carbon energy conservation and emission reduction [22,23], recycling of waste products [24,25], and old for new [26,27]. For example, the study of Wang et al [28] showed that government subsidy has improved the overall operating efficiency of the closed-loop supply chain of low-carbon E-commerce and the total social surplus.…”
Section: Government Subsidy Policymentioning
confidence: 99%